Seismic behavior of 1960's RC buildings exposed to marine environment. (August 2018) - Bru, David; González, Antonio; Baeza, F. Javier; Ivorra, Salvador
Abstract: Steel rebars corrosion is one of the most important problems of reinforced concrete (RC) structures. The mechanical performance loss of RC elements because of steel corrosion can be aggravated under horizontal loads (e.g. wind pressure or seismic actions). This paper presents a methodology for the study of the seismic behavior of a residential typology of the Mediterranean coast, which was widely spread during the 1960's. These RC frame structures are usually 10 to 15 stories high, located very close to the coast and are exempt buildings, which made them specially exposed to chloride corrosion. Besides, there are some design conditions that should be taken into account: (i) these structures were designed only under gravity loads, especially seismic actions were not considered. (ii) The raw materials had lower quality than those considered in current design codes, e.g. structural concrete strength was around 15 MPa, and made with natural beach sand as fine aggregates (hence including chlorides into the concrete mass). Therefore, two important aspects converge in these buildings, fifty years of marine exposure (i.e. degradation by corrosion) and the omission of the seismic loads in the original design, making them especially vulnerable to earthquakes (in an area with a moderate-high seismicity). Hence, a methodology for the seismic analysis of the corroded structure is proposed, in order to determine the structural safety factor of this type of structures, and evaluate the effectiveness of a retrofitting if necessary. Highlights: Methodology to evaluate seismic behaviour of old concrete buildings Plastic-Hinge capacity modifications along service life in marine environments Ductility reduction due to corrosion effects Non-linear seismic analysis of damaged concrete buildings Qualitative and quantitative evaluation of a real 39 m tall concrete building